Selected works of Cheng Siwei economic reforms and development in China - Cheng, Siwei (Enrich Professional Publishing Pvt Ltd, 2011)
The author outlines his theories for bringing economic reform to China in the context of a global economy. Using the principles of complexity science and finance, the author also elaborates on the characteristics and laws of fictitious economy in China and from this perspective, studies such issues as venture capital, financial crises, capital and monetary markets, inflation and deflation, housing system reform, the social security system and enterprise management in contemporary China. The book has been highly regarded by top-ranked Chinese politicians and distinguished scholars and is essential reading for anyone wishing to understand the economic complexities of the development of China.